Joachim Brohm : Areal: ein fotografisches Projekt 1992 - 2002. - Fotomuseum Winterthur; Westfälischer Kunstverein, Münster; Fotomuseum im Münchner Stadtmuseum, München (Göttingen : Steidl Verlag, 2002)
Joachim Brohm undertook a photo-urban project of long term observation. For roughly a decade, from 1992 to 2002 - he took photographs of the same location - on the outskirts of a German city - as it was being redeveloped from a 1950s commercial / industrial district into a gentifried post industrial services centre and living area. In a meditative return, Brohm cartographically captured the premises, their buildings and materials, and chronologically documented the changes and developments during this period. Brohm's pictorial idiom - characterised by a dissolved centre, layering and compositions referring to the continuations of space beyond the picture's limts - is both documentary and deconstructive. His photographs simultaneously depict and dissolve the outside world, lending the transitory, hovering state of reality and meaning a powerful pictorial form.
biog. p. 262
Joachim Brohm: Areal, Fotomuseum Winterhur / Westfälischer Kunstverein, Münster / Fotomuseum im Stadtmuseum, München
Duits
Engels
boek
Keywords: Brohm, Joachim